Exploration of CviR-mediated quorum sensing inhibitors from Cladosporium spp. against Chromobacterium violaceum through computational studies - Mahadevamurthy Murali; Faiyaz Ahmed; Hittanahallikoppal Gajendramurthy Gowtham; Jamiu Olaseni Aribisala; Rukayat Abiola Abdulsalam; Ali A. Shati; Mohammad Y. Alfaifi; R. Z. Sayyed; Saheed Sabiu; Kestur Nagaraj Amruthesh (Scientific Reports, 2023)
Abstract An opportunistic human pathogenic bacterium, Chromobacterium violaceum resists the potency of most antibiotics by exploiting the quorum sensing system within their community to control virulence factor expression. Therefore, blocking the quorum sensing mechanism could help to treat several infectious caused by this organism. The quorum sensing receptor (CviR) of C. violaceum was used as a model target in the current investigation to identify potentially novel quorum sensing inhibitors from Cladosporium spp. through in silico computational approaches. The molecular docking results confirmed the anti-quorum sensing potential of bioactive compounds from Cladosporium spp. through binding to CviR with varying docking scores between – 5.2 and – 9.5 kcal/mol. Relative to the positive control [Azithromycin (– 7.4 kcal/mol)], the top six metabolites of Cladosporium spp. had higher docking scores and were generally greater than – 8.5 kcal/mol. The thermodynamic stability and binding affinity refinement of top-ranked CviR inhibitors were further studied through a 160 ns molecular dynamic (MD) simulation. The Post-MD simulation analysis confirmed the top-ranked compounds' affinity, stability, and biomolecular interactions with CviR at 50 ns, 100 ns, and 160 ns with Coniochaetone K of the Cladosporium spp. having the highest binding free energy (– 30.87 kcal/mol) and best interactions (two consistent hydrogen bond contact) following the 160 ns simulation. The predicted pharmacokinetics properties of top selected compounds point to their drug likeliness, potentiating their chance as a possible drug candidate. Overall, the top-ranked compounds from Cladosporium spp., especially Coniochaetone K, could be identified as potential C. violaceum CviR inhibitors. The development of these compounds as broad-spectrum antibacterial medicines is thus possible in the future following the completion of further preclinical and clinical research.